Letter from J.W. Thomas to James Curtis Booth, March 25, 1882 - Thomas, Joseph W. (1882)
Joseph W. Thomas writes to James Curtis Booth (1810-1888) regarding trees.
Keywords: Booth, James Curtis, 1810-1888; Nurseries (Horticulture); Thomas, Joseph W.